Odpowiedź :
Odpowiedź:
Zad. 4
a) dla x = 2, y = - 1
5x - 2y = 5 • 2 - 2 • ( - 1) = 10 + 2 = 12
b) dla x = - 12, y = - 114
5x - 2y = 5 • ( - 12) - 2 • ( - 144) = - 60 + 288 = 228
c) dla x = - 0,2 y = 1,5
5x - 2y = 5 • ( - 0,2) - 2 • 1,5 = - 1 - 3 = - 4
Zad. 5
a) - 2x + 6x = 4x
b) 23b • 0,75 = 17,25b
c) - 12a - 20a = - 32a
d) - 3c + 2c - 20c = - 21c
e) - 5t - ( - 4t ) - 7t = - 5t + 4t - 7t = - 8t
f) ( - 6 ) • 7y = - 42y
g) 9z • 23 = 207z
h) ( - 33z ) : ( - 2,2) = 15z
Odpowiedź:
Zad 4
a) 5 *2 –2 * (-1) = 10 - (-2) = 10 + 2 = 12
b) 5 * (-12) –2 * (-114) = -60 - (-228) = -60 + 228 = 168
c) 5 * (-0,2) - 2 * 1,5 = -1 - 3 = -4
Zad 5
a) -2x + 6x = 4x
b) 23b ꞏ 0,75 = 17,25b
c) -12a –20a = -32a
d) -3c + 2c –20c = -1c - 20c = -21c
e) -5t –(-4t) -7t = -5t + 4t - 7t = -1t - 7t = - 8t
f) -6 ꞏ7y = - 42y
g) 9z ꞏ23= 207z
h) (-33z) : (-2,2) = 15z